Association of optic nerve sheath lesion and brain or meningeal metastasis caused by lung cancer. Issue 15 (14th June 2022) - Song, Shuai; Chang, Dong; Li, Hao; Liu, Chunquan; Cui, Yong; Li, Hongyang
Abstract: Background: With the development of imaging, the etiology of ocular lesions caused by lung cancer was not found only intraocular. Neuro‐ophthalmological imaging has been found to be useful for the diagnosis of meningeal carcinomatosis, although few studies have previously been published. Our study used magnetic resonance imaging (MRI) to determine if there was a the relationship between ocular symptoms and lung cancer metastasis. Methods: We carried out a retrospective analysis which included patients with ocular lesions and lung cancer on which orbit MRI was performed together with ocular examination during January 2014 to January 2022. Here, we describe the characteristics of intraocular metastasis and optic nerve sheath lesions. Results: A total of 21 lung cancer patients had ocular lesions, of which eight cases had choroidal metastasis; a further eight patients had optic nerve sheath lesions. There was one case (12.5%) of choroidal metastasis with brain or meningeal metastasis, and eight cases (100%) with optic nerve sheath lesions with brain or meningeal metastasis. A total of 75.0% patients with choroidal metastasis did not have any history of known lung cancer, and 25.0% of optic nerve sheath lesions in patients were found before a meningeal metastasis diagnosis. The features of optic nerve sheath lesions included thickening and strengthening of the long segment of the orbital optic nerve sheath with a clear boundary. Conclusions: The pathway of choroidal and optic nerve sheath lesions was different. Optic nerve sheath lesions were associated with brain and meningeal metastasis. When lung cancer‐induced meningeal metastasis is suspected, orbital MRI is recommended to assist in the diagnosis. Abstract : Diagnosis of the latent brain or meningeal metastasis of lung cancer patients is problematic. We found that optic nerve sheath lesions were associated with brain or meningeal metastasis of lung cancer. The imaging of optic nerve sheath lesions by orbit MRI may be beneficial for diagnosing latent brain or meningeal metastasis of lung cancer patients at an early stage.